Microenvironment Interactions in Chronic Lymphocytic Leukemia: A Delicate Equilibrium Linking the Quiescent and the Proliferative Pool - Palacios, F.; Abreu, C.; Moreno, P.; Giordano, M.; Gamberale, R.; Oppezzo, P. (IntechOpen, 2012)
None